MLPA for confirmation of array CGH results and determination of inheritance - Hills, Alison (BioMed Central, 2010)
BACKGROUND: Array CGH has recently been introduced into our laboratory in place of karyotype analysis for patients with suspected genomic imbalance. Results require confirmation to check sample identity, and analysis of parental samples to determine inheritance and thus assess the clinical significance of the abnormality. Here we describe an MLPA-based strategy for the follow-up of abnormal aCGH results. RESULTS: In the first 17 months of our MLPA-based aCGH follow-up service, 317 different custom MLPA probes for novel aCGH-detected abnormalities were developed for inheritance studies in 164 families. In addition, 110 samples were tested for confirmation of aCGH-detected abnormalities in common syndromic or subtelomeric regions using commercial MLPA kits. Overall, a total of 1215 samples have been tested by MLPA. A total of 72 de novo abnormalities were confirmed. CONCLUSIONS: Confirmation of aCGH-detected abnormalities and inheritance of these abnormalities are essential for accurate diagnosis and interpretation of aCGH results. The development of a new service utilising custom made MLPA probes and commercial MLPA kits for follow-up studies of array CGH results has been found to be efficient and flexible in our laboratory.